Abundancia de postlarvas del camarón blanco Penaeus vannamei (Decapoda: Penaeidae) en el litoral del Sur de Sinaloa, México, 1984-85 - Solís-Ibarra, R (Universidad de Costa Rica, 1993)
Spatial and temporal variations of postlarval white shrimp (Penaeus vannamei), were studied from Nov. 1984 to Oct. 1985 in the coastal rone near the Presidio River moutb, Sinaloa, Mexico (230 06'N, 1060 18'W). Twenty four sampling trips were carried out Plankton nets witb a 500 microos mesh aperture were used and 4715 postlarvae were collected. Postlarval occurrence generally followed a similar abundance panem to tbat described for tbe neighbourlng costallagoon system. Regarding spatial variation, abundance was greater closer to the shore. Postlarval density was significantly higher near tbe bottom tban at tbe surface. Postlarval numbers were higher during the rainy scason and higher postlarval densities were recorded at full moon.